Judicial Reform and Human Security in West Africa: Comparative Lessons from Ghana and Sierra Leone - Thomas Sheku Marah (Gloria Justitia, 2026)
This article examines the relationship between judicial reform, access to justice, and human security through a comparative analysis of Sierra Leone and Ghana between 2010 and 2024. Existing scholarship on African judicial reform has largely focused on institutional modernization, legal independence, and governance efficiency, while giving comparatively limited attention to how judicial performance shapes broader human-security outcomes such as public trust, legal protection, and procedural inclusion. Drawing on the Human Security Framework and Access to Justice Theory, the study employs a qualitative comparative methodology based on doctrinal analysis, policy documents, judicial reform strategies, governance reports, and court-performance materials. The findings demonstrate significant divergence in reform outcomes between the two countries. Ghana’s investments in digital case management, procedural transparency, and judicial administration have improved institutional responsiveness and public confidence, although challenges of digital inequality and uneven accessibility remain. By contrast, Sierra Leone continues to face structural constraints linked to limited institutional capacity, weak enforcement mechanisms, underfunding, and low technological integration. The article argues that judicial reform contributes to human security only when institutional modernization is accompanied by accessible, enforceable, and socially inclusive justice systems. It contributes to comparative governance scholarship by linking justice-sector reform to human-security outcomes in post-conflict African democracies.